Actualization of Mui Fatwa on Positive Law as Islamic Legal Opinion in Indonesia - May Shinta; Namira Rosalina Mutian (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2022)
Legal opinion in Islam will discuss issues related to religious law such as fatwas. In Indonesia, there is a fatwa-making body called the MUI (Indonesian Ulema Council) which was established on July 26, 1975. This study uses the library research method by reviewing several libraries and comparing them with other literacy to find the right research results. The results of the study indicate that fatwas have an important role by becoming several national laws in the realm of Islamic economics. This is proven in the Supreme Court Regulation No. 2 concerning the Compilation of Sharia Economic Law (KHES), in addition to that regarding Islamic banking, for example PBI No. 9/19/PBI/2007. In addition, regarding sharia principles, the finance minister asked the MUI fatwa as the basis for issuing State Sharia Securities (SBSN).